Development of a laboratory CHILDCARE CENTER: An institutional practice in infusing the process of societal and organizational change in line with program PERMATA NEGARA - Hanafi, Zahyah; Valdez, Nena P.; Ng, Lee Luan (Universiti Utara Malaysia, 2013)
The objective of this study is to document the practices of PERMATA educators at seven PERMATA Centers under study.In addition, the study will focus on the learning and teaching experiences of all the stakeholders, they are the educators, parents, children and community.The study examined seven PERMATA centers on their structural and process quality that exists in each of the center. These are captured in the form of interviews, observations and documents.Firstly, all PERMATA centers under study have a standard infrastructure; a purpose built childcare center or a single bungalow. Within these centers you see ample space for activities, setting up corners (music, reading), rooms for different purposes (store, surau, kitchen), toilets and bathroom for boys and girls, wash area, and multi-functional indoor and outdoor properties spaces for creative play.All these reflect the emphasis on conducive and quality environment in the PERMATA centers. Secondly, PAPN has its own PERMATA curriculum and is used in all the PAPN centers throughout the country. The educators based their practices on modules which covers two areas: caring/nurturing and learning.These two areas covers six aspects: health and cleanliness, healthy food, exercise and well-being, care for safety and environment, train to managing oneself, and routine and transition. These areas are then translated into practices which are in module forms.There are also guidelines on the implementation of activities according to age group.Thus, PAPN has a curriculum which covers all the various development in the child that will enable it to develop a holistic child.The data collected revealed that these PAPN centers do have documents that showed the educators were qualified as they possessed a degree (irrespective of the area) and undergone a six weeks training on PERMATA program.In addition, there are also those with limited experience working in childcare centers. This reflects the seriousness of the government to ensure the PERMATA children are handled by educators who are not only passionate but qualified to handle the children.Studies have stressed this criteria as a vital aspect in childcare development; providers, educators, teachers with qualified educational background.Qualified educators tend to know their responsibilities and roles. Thus, the seven centers displayed their organizational chart, information on children’s’ enrolment, time table, menu, as well as children’s work and activities were all found on the walls in each of the center.This enables parents and community providers know the schedule and happenings at the center. This information is also a way of communicating with other stakeholders on current situation at the center.It allows parents and others to have a better understanding of the running of the PERMATA center.Once parents are aware and understand the rules and regulations at the PERMATA center then it would be easier for them to get involved.Parental involvement is a unique feature in PERMATA.Parents are required to be present at the center four hours a month or an hour a week. During this time parents and guardians get involved in many ways.There were those who helped with the domestic chores at the center, while others assisted the educators to bath, dress and feed the children.A few were seen directly involved in the children’s activities such as teaching and playing with the children and prepare instructional materials.Parental involvement is an important feature of a quality childcare center.Centers that nurture parents’ involvement has shown to produce children who are socio-emotionally stable, more confident and enjoy going to school. PERMATA belief in this and have organized a parent-teacher committee that becomes a platform for educators and parents to work together at the center.Community providers are an additional support to the educators and parents at PAPN.These comprised the professionals and specialists; banking institutions, medical and dental team, local library.Dental and health talk are a routine at the centers but these are actually the initiative of the medical department which renders free public services to the community. However, this opportunity has allowed parents to learn health practices which they can perform at home with the children.Similarly, the local library provides activities for children and the educators utilize this service for the development of the children.Thus, community-PAPN relationship provides activities that not only benefit the children but also educate the parents. These activities enriched the curriculum and presents learning opportunities for children at PAPN.Finally, the researchers proposed that PAPN centers could be set as the PERMATA Laboratory Childcare Center in states or districts where it is located.This is based on the findings that revealed PAPN as a childcare center that fulfils most of the criteria of a quality centre.Even though PAPN has all the aspects that qualify it as a quality childcare center however, there is still room for improvement.Suggestions and recommendations are made to ensure PAPN maintains the “best” practices.